Experimental Study on Two-Phase Flow Pattern of Air-Mixture of Distilled Water and 2% Butanol in Horizontal Mini Channel - Kumolosari, Eli; Sudarja; Indarto; Deendarlianto; Hermawan (Science & Technology Asia, 2024)
Two-phase flow occurs in many modern mini-sized objects. The two-phase flow pattern plays a crucial role in establishing the convection coefficient (h) for both heat transfer and pressure drop (△P). The current research examined the two-phase flow pattern in a transparent mini channel with an internal diameter of 1.6 mm. The orientation of the channel was horizontal. The fluids used were air-mixture of distilled water and 2% butanol with the liquid surface tension value of 46.03 mN/m. Superficial velocities of liquid and gas were varied in the range of 0.033 - 4.935 m/s and 0.066 - 66 m/s, respectively. The flow patterns observed were churn, annular, plug-annular, bubbly, and plug. The research also generated a flow pattern map. This map then was compared to those from certain preceding researchers. The findings indicated that the flow pattern map generated in this investigation was only consistent with the one established by Triplett et al. [1] with the exception of the transition boundary from plug flow and bubbly flow to churn flow. The dissimilarity was predicted due to the distinct surface tension of liquid employed. These findings contributed to discover the flow pattern characteristics which are applicable to the cooling performance of microelectronic cooling system, the efficiency of chemical reaction, etc.